The silence of bones - Hur, June (New York : Square Fish, 2020)
In Joseon Dynasty-era Korea, sixteen-year-old Seol, an indentured servant within the police bureau, becomes entangled in a politically-charged investigation into the murder of a noblewoman.
Keywords: Police -- Fiction; Indentured servants -- Fiction; Murder -- Fiction; Siblings -- Fiction; Catholics -- Fiction; Persecution -- Fiction; Mystery and detective stories; Korea -- History -- v